ASSESSMENT OF PIGS BY BLUP METHOD IN THE HERDS BREEDING FARM OF CHERKASSY AREA - Небилиця, М. С. (Scientific Progress & Innovations, 2013)
The first assessment results of young pigs of large white breed of pedigree farms of the region by BLUP method are presented. The correlation coefficients between indicators of different methods of assessment and core breeding signs, when animals are removed from the control of cultivationare defined. It is found that the rate of assessment of pigs by BLUP method is strongly correlated with the indicators of the index, the rank and evaluation by independent levels. However, higher correlation coefficients with estimated indices of the daily increase of live weight of pigs and thickness of pork fat (r = 0,52) and energy growth and thickness of pork fat (r = 0,40) is installed.